Improvement of hemodynamic parameters in aortic stenosis patients with transcatheter valve replacement by using impedance cardiography - Wan, Luqing; Tang, Jianjun; Xiao, Yanchao; Li, Hui; Peng, Zengjin; Xu, Dan-Yan; Shen, Li (Frontiers in Cardiovascular Medicine, 2022)
Background: The hemodynamic changes of patients with aortic stenosis (AS) who underwent transcatheter valve replacement (TAVR) have not been completely investigated. Methods and results: We enrolled 74 patients with AS who underwent TAVR and assessed cardiac function changes at 1-week post-operation by impedance cardiography (ICG) in a supine position at rest for more than 15 minutes. Of the 74 patients, 47 had preserved left ventricular ejection fraction (LVEF ≥ 50%; preserved-LVEF group), and 27 had reduced LVEF (LVEF < 50%; reduced-LVEF group). TAVR improved the cardiac structure and function, as evidenced by the decrease in the left ventricular end-diastolic (LVED), left atrial diameter (LAD), and an increase in the LVEF. We observed a decrease of N-terminal pro-brain natriuretic peptide (NT-proBNP) level compared to that before treatment. Moreover, patients with reduced LVEF had more significant reduction of NT-proBNP than those with preserved LVEF. Meanwhile, the blood pressure of patients had no significant differences pre- and post-operation. Based on ICG, there were no changes in parameter of cardiac preload (thoracic fluid content (TFC)). We observed an improvement in parameters of diastolic cardiac function (left ventricular ejection time (LVET), pre-ejection period (PEP)). And we detected converse results in parameters of heart systolic function (systolic time ratio (STR), cardiac output (CO), cardiac index (CI), stroke index (SI), and stroke volume (SV)), and cardiac afterload (stroke systemic vascular resistance (SSVR), SSVR-index (SSVRI)). In addition, TFC level was decreased in patients with thoracic volume overload after valve replacement. Subgroup analysis showed that the changes in those parameters were more noticeable in patients with reduced LVEF than that with preserved LVEF. Moreover, we observed no effects on parameters of heart systolic function and heart afterload in the LVEF ≥ 50% group before and after TAVR. Conclusion: Our data revealed a beneficial effect of TAVR in diastolic function and preload as detected by the ICG. But the LV systolic function and cardiac afterload were not improved in patients with LVEF < 50%. The result indicated that ICG could be used as an important technique to monitor cardiac condition of patients after aortic valve replacement.